Measurement of Photoreceptor Layer in Glaucoma: A Spectral-Domain Optical Coherence Tomography Study - Ning Fan; Nina Huang; Dennis Shun Chiu Lam; Christopher Kai-shun Leung (Journal of Ophthalmology)
Objective. To measure and compare photoreceptor layer thickness between normal and glaucomatous eyes using spectral-domain optical coherence tomography (OCT). Methods. Thirty-eight healthy normal volunteers and 47 glaucoma patients were included in the analysis. One eye from each participant was randomly selected for macula imaging by a spectral-domain OCT (3D OCT-1000, Topcon, Tokyo, Japan). The foveal and parafoveal (1.5 mm from the fovea) outer nuclear layer (ONL) and inner and outer segments (IS+OS) layer thicknesses were measured by a single masked observer. The measurements were repeated 3 times in a random sample of 30 normal eyes to determine the repeatability coefficient and intraclass correlation coefficient. Results. The measurement variabilities of photoreceptor thickness were low. The respective intraclass correlation coefficients of ONL and IS+OS thicknesses were 0.96 (95% confidence interval: 0.94–0.98) and 0.82 (95% confidence interval 0.70–0.90). While there were no differences in parafoveal ONL and IS+OS thicknesses between normal and glaucoma groups (𝑃≤.410), the foveal ONL thickness was greater in glaucomatous eyes (𝑃=.011) than in normal eyes. Conclusions. Glaucomatous damage may involve structural change in the photoreceptor layer.